The Long Pentraxin PTX3 Is of Major Importance Among Acute Phase Proteins in Chickens - Burkhardt, Nina B.; Röll, Susanne; Staudt, Anke; Elleder, Daniel; Härtle, Sonja; Costa, Taiana; Alber, Andreas; Stevens, Mark P.; Vervelde, Lonneke; Schusser, Benjamin; Kaspers, Bernd (Frontiers in Immunology, 2019)
The expression level of acute phase proteins (APPs) mirrors the health status of an individual. In human medicine, C-reactive protein (CRP) and other members of the pentraxin family are of significant relevance for assessing disease severity and prognosis. In chickens, however, which represent the most common livestock species around the world, no such marker has yet gained general acceptance. The aim of this study was therefore, to characterize chicken pentraxin 3 (chPTX3) and to evaluate its applicability as a general marker for inflammatory conditions. The mammalian and chicken PTX3 proteins were predicted to be similar in sequence, domain organization and polymeric structure. Nevertheless, some characteristics like certain sequence sections, which have varied during the evolution of mammals, and species-specific glycosylation patterns, suggest distinct biological functions. ChPTX3 is constitutively expressed in various tissues but, interestingly, could not be found in splenic tissue samples without stimulation. However, upon treatment with lipopolysaccharide (LPS), PTX3 expression in chicken spleens increased to 95-fold within hours. A search for PTX3 reads in various publicly available RNA-seq data sets of chicken spleen and bursa of Fabricius also showed that PTX3 expression increases within days after experimental infection with viral and bacterial pathogens. An experimental infection with avian pathogenic E.coli and qPCR analysis of spleen samples further established a challenge dose-dependent significant up-regulation of chPTX3 in subclinically infected birds of up to over 150-fold as compared to untreated controls. Our results indicate the potential of chPTX3 as an APP marker to monitor inflammatory conditions in poultry flocks.